Inter-industry Wage Differences and Individual Heterogeneity: How Competitive is Wage Setting in the UK? - Alan Carruth; Bill Collier; Andy Dickerson (University of Kent, Department of Economics, 1999)
There are two findings that are conspicuous in almost all studies of individual wage determination. First, standard cross-section wage equations rarely account for more than half of the total variance in earnings between individuals. Second, there are large and persistent inter-industry wage differentials and these are frequently attributed to non-competitive forces in wage determination. This paper explores these two issues using cross-section, pooled and panel data drawn from the first six waves of the British Household Panel Survey. We show that much of the residual variation in wages can be explained by significant unobserved differences between workers, perhaps reflecting innate ability or other characteristics of individuals not captured by observed data. Moreover, our wage equations explain a substantial proportion of the variation in earnings between individuals in terms of their observed and unobserved characteristics, and we find only a small role for job characteristics and almost no role for industry affiliation once we allow for unobserved individual heterogeneity. One interpretation of our findings is that wages are determined principally by individual characteristics - as human capital theory presupposes - rather than by compensating differentials or by non-competitive factors.
Keywords: C21; C23; J31; 330; Wage Structure; Wage Differentials; Panel Data; Lohn; Lohnstruktur; Branche; Vergleich; Großbritannien